The Composition Effect of Consumption around Retirement: Evidence from Singapore - Agarwal, Sumit; Pan, Jessica; Qian, Wenlan (American Economic Review, 2015)
It is well established that consumption is “hump” shaped over an individual's lifecycle, peaking in middle age and then declining in the years that follow. Prior research has documented that consumption declines at retirement, which is inconsistent with the standard lifecycle model with consumption smoothing. Using a unique dataset with detailed administrative records of credit and debit card transactions, we show the hump shaped lifecycle consumption pattern as documented in the literature. Additionally, we show compositional changes in consumption expenditures across individuals in the years surrounding retirement confirming the results of Aguiar and Hurst (2005, 2013).